PENGARUH KARAKTERISTIK PERUSAHAAN, RASIO KEUANGAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN - JOVINDO ELDWIN HARTONO; ARIES JONATHAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The purpose of this research is to obtain empirical evidence about the effect of profitability, company size, liquidity, activity ratio, capital structure, institutional ownership, sales growth, and firm age on firm value. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from year 2021 until year 2023. The sampling method in this study uses purposive sampling method with 81 companies and 243 data that will be used as research samples. The sample data obtained will be analyzed using multiple linear regression. The results of this research indicate that profitability, liquidity, capital structure, and firm age affect firm value. Firm age has a positive effect on firm value, companies that have been established for a long time usually have larger assets so that they are more trusted by investors which in turn will increase company value. Other independent variables, namely company size, institutional ownership, sales growth, and activity ratio have no effect on firm value.